Azalea Leafminer, Caloptilia azaleella (Brants) (Insecta: Lepidoptera: Gracillariidae) - G. W. Dekle (EDIS)
EENY-379, a 5-page illustrated fact sheet by G. W. Dekle, is part of the Featured Creatures collection. It provides information about this larva of a tiny purple- and yellow-marked moth which is a pest of container- and field-grown azalea nursery stock. Includes references. Published by the UF Department of Entomology and Nematology, June 2007.